Pengaruh Pendidikan, Rasio Belanja Modal dan Pekerja Informal terhadap Tingkat Kemiskinan di Provinsi Nusa Tenggara Timur Tahun 2019-2024 dengan Covid-19 sebagai Variabel Dummy - Kurnianti, Hesti Dwi; Herlitah, Herlitah; M, Saparuddin (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
This study aims to analyse the effect of education, capital expenditure, informal workers, and the COVID-19 pandemic on the poverty rate in East Nusa Tenggara Province during the 2019–2024 period. A quantitative approach was applied using panel data regression analysis with a census technique on the entire population of 22 regencies/cities, yielding 132 observations. Utilizing secondary data from BPS and DJPK, the analysis included classical assumption tests, multiple linear regression, and hypothesis testing. The results indicate that education and informal workers have a negative and significant effect on poverty levels. Education improves community productivity, while, the informal sector still serves as the primary source of livelihood for people in East Nusa Tenggara Province. Conversely, capital expenditure does not have a significant impact on poverty because its effectiveness depends not only on the size of the budget, but also on the quality of management and the development benefits generated. Meanwhile, the COVID-19 pandemic had a positive and significant effect on increasing poverty due to economic disruptions and job losses. These findings imply the need for integrated policies prioritizing education quality, informal sector empowerment, capital expenditure effectiveness, and social protection. Future studies are recommended to add relevant variables such as the human development index, unemployment, or income inequality, and to extend the research period to comprehensively capture long-term impacts.